2019
DOI: 10.1111/mmi.14375
|View full text |Cite
|
Sign up to set email alerts
|

Flocculation of Saccharomyces cerevisiae is dependent on activation of Slt2 and Rlm1 regulated by the cell wall integrity pathway

Abstract: Summary Flocculation is an essential characteristic of yeast cells required for survival under adverse conditions. The multicellular structure (flocs) of yeast provides a suitable microenvironment to enhance the chances of survival during stress conditions. Although the signaling events triggering flocculation have been studied earlier, molecular mechanisms remain elusive. In the present study, we used flocculating sen1 mutants to identify the mechanism of flocculation. Based on the abnormal cell surface morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 93 publications
(140 reference statements)
1
13
0
Order By: Relevance
“…The Slt2-MAPK regulated cell-wall integrity was verified in multiple fungi, including Trichoderma spp., , Metarhizium robertsii, Penicillium digitatum, and S. cerevisiae . However, two types of MAPK (Fus3 and Slt2) of strain TC967 were both involved in CWI.…”
Section: Discussionmentioning
confidence: 99%
“…The Slt2-MAPK regulated cell-wall integrity was verified in multiple fungi, including Trichoderma spp., , Metarhizium robertsii, Penicillium digitatum, and S. cerevisiae . However, two types of MAPK (Fus3 and Slt2) of strain TC967 were both involved in CWI.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, it has been shown that the phosphorylation of Slt2 but not its catalytic activity is required for flocculation, suggesting that Slt2 probably acts as a transactivator to induce transcription of FLO genes binding to their promoters via Rlm1, independently of its catalytic activity [157]. The binding of Rlm1 reduces the occupancy of the Tup1 repressor leading to the recruitment of TBP and Pol II at the promoters of FLO genes in flocculating cells.…”
Section: Transcriptional Activation Mechanism For Rlm1-dependent Genesmentioning
confidence: 99%
“…The binding of Rlm1 reduces the occupancy of the Tup1 repressor leading to the recruitment of TBP and Pol II at the promoters of FLO genes in flocculating cells. Antagonistic binding of Rlm1 and Tup1, and the presence of overlapping binding sites at the promoters of FLO genes suggest that the Rlm1 and Tup1 interplay is involved in the regulation of FLO gene expression and yeast flocculation [157] The ability of Slt2 to drive gene expression by itself is explained by the fact that Slt2 physically interacts with RNA Pol II upon cell wall stress. Slt2 is first recruited to promoters by Rlm1 to interact with RNA Pol II, to move from the transcription initiation complex to the transcription elongation complex at the coding region in a second step, independently of Rlm1 (Figure 3).…”
Section: Transcriptional Activation Mechanism For Rlm1-dependent Genesmentioning
confidence: 99%
“…2.2 | BSC2 participates in cell surface remodelling during biofilm formation in S. cerevisiae Bojsen et al (2014) have reported that the biofilm is associated with MDR strains. A key feature of biofilms in the model yeast is hydrophobicity (CSH), which linked to the flocculation seen in S. cerevisiae biofilms (Sariki, Kumawat, Singh, & Tomar, 2019). In order to investigated whether the biofilm formation is seen in the multidrug-resistant BSC2 strain, we examined flocculation capacity and levels of CSH and biofilm formation in BY4741, bsc2Δ and BSC2 overexpression strains.…”
Section: Bsc2 Is Related To Mdrmentioning
confidence: 99%